2022
DOI: 10.31234/osf.io/k6g5d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Gender Gap in the Care Economy is Larger in Highly Developed Countries: Socio-cultural Explanations for Paradoxical Findings

Abstract: Despite the growing importance of care economy careers (e.g., healthcare and education), men remain underrepresented in these fields. Past research suggests that, while economically developed nations tend to support equal rights for men and women, their labor markets tend to be highly gender-segregated (Charles 1992; 2003). By examining this paradoxical pattern in the care economy, we asked whether men’s lower interest in care economy careers is more pronounced in highly economically developed countries (vs. e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Lastly, the gender equality paradox is an emerging phenomenon that has gained substantial scientific support across subjects ( Falk and Hermle, 2018 ; Campbell et al, 2021 ; Block et al, 2022 ; Vishkin, 2022 ). It requires attention from both the scientific community and the public because attempting to close gender gaps following traditional social-role theories and applying conventional methods, might end up exacerbating gender variations.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the gender equality paradox is an emerging phenomenon that has gained substantial scientific support across subjects ( Falk and Hermle, 2018 ; Campbell et al, 2021 ; Block et al, 2022 ; Vishkin, 2022 ). It requires attention from both the scientific community and the public because attempting to close gender gaps following traditional social-role theories and applying conventional methods, might end up exacerbating gender variations.…”
Section: Discussionmentioning
confidence: 99%
“…Yet this pattern is not universal. A recent large-scale, multinational analysis showed that in less economically developed non-Western countries, men engage in communal roles like caretaking while also maintaining their agency in other domains (Block et al, 2022). Given this observed difference in how masculinity is presented and performed across cultures, we wonder whether men in cultures with broader notions of masculinity might experience less discrepancy, conformity pressure, and threat responsivity.…”
Section: Empirical Theoretical and Practical Implications And Conside...mentioning
confidence: 99%